(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
This study was carried out to determine the influence of Job Security (JS) on LP in PPs in south west Nigeria. Descriptive design was used. Multi-stage sampling procedure was adopted. Four states (Ondo, Ogun, Osun and Lagos) that had federal and state polytechnics were purposively selected, while the four federal polytechnics were enumerated and non-proportional to size technique was used to select six state polytechnics. Proportionate to size was used to select 540 Lecturers, seventy (70) Heads of Department(HoDs) and nine hundred and twenty-three (923) students. The instrument used were LP and JS questionnaires for Lecturers, HoDs and students. The study’s reliability of the instrument on LP and JS was r=0.68. TQ and Students Project Supervision’s reliability result were r=0.73 & r=0.70 for lecturers and students questionnaires respectively. Descriptive statistics of frequency counts, simple percentages, mean and standard deviation was used to analyse the three research questions raised. The CS (=2.34) was low, 74.1% of lecturers did not publish in textbooks, while TQ (=2.89; = 2.89; = 2.93) and lecturers’ commitment to SsPS (=2.85; = 2.89; = 2.77) as rated by lecturers, HoDs and students respectively were moderate in PPs. Salary ( =2.15) implies that lecturers are not satisfied with their salary payment; CsS (= 2.30), this result implies that lecturers are not satisfied with the conditions of service in their various polytechnics. Job security enhanced lecturers’ productivity in public polytechnics in southwestern Nigeria. Therefore, government should increase subvention, research grant and conditions of service to public polytechnics’ lecturers for improved productivity.